The Evolution of Façades and Interior Layouts of Narrow-Front Townhouses - Avi Friedman (Vitruvio: International Journal of Architectural Technology and Sustainability)
What made the narrow townhouse, narrower than 20 ft (6 m), a suitable structure for public markets in medieval times, a dwelling for the nobility in the Renaissance, and a type of affordable housing in the modern era? Massey & Maxwell regard the townhouse as a type of building, rather than a building style. This observation lay the foundation that explains how the townhouse adapted to fit particular time periods and geographical locations, and their respective aesthetics values. While the building has remained structurally identical, it has undergone manipulations of interior room layout and exterior expression. Despite the differences in style, material, ornamentation, and detail over their history, townhouses all share one common property: the continuous façade of several joint units. By examining variations of narrow-front townhouses this paper establishes what factors or elements were responsible for its evolution. The author concludes that the design survived changes in economic conditions and social values, and political upheaval due to the inherent adaptability of its basic form, remaining part of the architectural context in every era.